Contemporary concepts of US foreign policy: opportunities and reality - Shamara, Irina; Kostandi, Diana (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 2020)
The article analyzes the current concepts of US foreign policy, the direction of US foreign policy, and examines the economic background of US foreign policy. In particular, the fundamental indicators of US economic development have been studied, which allow the state to be a regional and world leader and pursue a hegemony strategy. The subject of research in the article is to determine the general and specific aspects of US foreign policy at the present stage. The goal is to determine the impact of US policy on the geopolitical transformation of the world. Objectives: the study of modern concepts of US foreign policy in the context of globalization and regionalization of the world. The study used the following general scientific methods: using the system analysis, the evolution of the US foreign policy in the globalization languages of the world was considered; In order to generalize the activities of various administrations and governments, compare their positions on shaping the country’s foreign policy, a comparative historical method was used. relationship. The following results were obtained: on the basis of the analysis of the current US policy, the political strategies of the United States in Europe and the Middle East were discovered and analyzed in detail. Conclusions: The United States remains the key actor in international relations at the present stage, and so far retains its influence on the processes in the world. US foreign policy is aimed at stabilizing international relations in such key regions as the Middle East and the EU. A comprehensive analysis of the presidents and their administrations suggests the continuity of US foreign policy in the Middle East. With the arrival of D. Trump, the foreign policy of American Republicans is saturated with power and cruelty.